2020
DOI: 10.1101/2020.08.10.243659
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Dissecting the microenvironment around biosynthetic scaffolds in murine skin wound healing

Abstract: Structural properties of biomaterials play critical roles in guiding cell behaviors and influence the immune response against them. In this study, we fabricated electro-spun membranes with three types of surface topography (Random, Aligned, and Latticed). The aligned membranes showed immunomodulatory ability, and led to faster wound healing, reduced fibrotic response and enhanced regeneration of cutaneous appendages. Based on that, we performed single-cell RNA sequencing analysis on cells of wounded mouse skin… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
2

Relationship

4
2

Authors

Journals

citations
Cited by 9 publications
(21 citation statements)
references
References 62 publications
(85 reference statements)
1
20
0
Order By: Relevance
“…After a series of in vitro studies, we applied a subcutaneous implantation model to evaluate effect of ion-doped hydroxyapatite on immune microenvironment as reported previously [ 35 ]. The critical-sized Sprague-Dawley (SD) rat cranial defect model was also used to evaluate the material's promoting effects on bone regeneration in vivo .…”
Section: Methodsmentioning
confidence: 99%
“…After a series of in vitro studies, we applied a subcutaneous implantation model to evaluate effect of ion-doped hydroxyapatite on immune microenvironment as reported previously [ 35 ]. The critical-sized Sprague-Dawley (SD) rat cranial defect model was also used to evaluate the material's promoting effects on bone regeneration in vivo .…”
Section: Methodsmentioning
confidence: 99%
“…Immune system such as macrophage and adaptive T cell is also sensitive to the surrounding mechanical cues [ 147 ]. In fact, every scaffold, once implanted in vivo , will elicit a definitive host immune response [ 148 ]. Up to date, the macrophage plasticity was found to exhibit a reciprocal polarization behavior depending on substrate stiffness [ 147 ], and pro-inflammatory response activated by engineered materials is also likely to contribute to the disrupted tissue remodeling via regulating the secreted extracellular vesicle of relevant cells [ 149 ].…”
Section: The Role Of Substrate Stiffness In Material-mediated Tissue ...mentioning
confidence: 99%
“…Aligned membranes could promote the normal differentiation and outgrowth of vascular smooth muscle cells [ 17 , 22 ]. Critically, previous research in our group has shown that aligned membranes have many advantages in soft tissue repair and can actively regulate the immune response [ 23 ].…”
Section: Introductionmentioning
confidence: 99%